FRI0065 Anti-tnf alpha monoclonal antibodies alter the activation and differentiation pattern of monocytes in patients with rheumatoid arthritis. (1st June 2001) - Müller, R; Skapenko, A; Wendler, J; Grünke, M; Kalden, JR; Schulze-Koops, H
Abstract : Background: Anti-TNFα monoclonal antibodies (mAbs) have recently been introduced as a treatment for rheumatoid arthritis (RA). Whereas anti-TNFα mAbs are potent inhibitors of inflammation, their effect on the activation and differentiation of myeloid cells has not been elucidated. Objectives: To investigate the function and the phenotype of monocytes from RA patients during their differentiation to macrophages in vitro before and 4 weeks after a single administration of mAbs to TNFα. Methods: Patients with highly active disease who were resistant to treatment with disease modifying antirheumatic drugs and corticosteroids were included into the study. Monocytes were isolated from the peripheral blood by negative selection, and their phenotype was analysed directly after isolation and during differentiation to macrophages. Results: Treatment was effective as 4 weeks after mAb application the inflammatory activity, as assesed by DAS 28, and the sedimentation rate were significantly reduced. Whereas the expression of HLA-DR, CD40, CD25, CD80, CD86, CD14 and CD68 in freshly isolated monocytes was similar before and after treatment with anti-TNFα, marked differences were found during maturation. After treatment, upregulation of HLA-DR and CD80 was markedly enhanced during macrophage differentiation. In contrast, the expression of CD40 was decreased after treatment. Conclusion: The results demonstrate that a single therapy with anti-TNFα mAbs alters the ability of macrophages to upregulate molecules involved in cellular inflammation even 4 weeks after treatment. However, as those changes were associated with clinical benefit, the data suggest that the clinical effect of anti-TNFα mAbs treatment is not restricted to neutralising TNFα but may be due to long lasting anti-inflammatory alterations that remain active even after the mAb has been cleared from the circulation.